INFLUENCE OF DIVIDEND POLICY, INVESTMENT DECISION, STRUCTURE CAPITAL, AND COMPANY SIZE, ON COMPANY VALUE - Aurellia Anjelia Sitorus; Rita Julianti Panjaitan; Wirda Lilia; Tika Indria (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2023)
The company is an organization that aims to gain profits or company profits continuously. This study aims to analyze the effect of dividend policy, investment decisions, capital structure, and company size on the value of manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange for the 2017-2021 period. In this research, this company used a purposive sampling technique with samples obtained by 75 companies in the consumer goods industry sector that were listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. In testing the hypothesis in this study, partial and simultaneous results can be obtained. The partial results in the research that has been done are that only the Capital Structure variable has an effect on Firm Value. As for the simultaneous results, the dividend policy, investment decisions, capital structure, and company size variables affect the company value variable in manufacturing companies in the consumer goods sector on the Indonesia Stock Exchange for the 2017-2021 period